2019
DOI: 10.1002/pip.3140
|View full text |Cite
|
Sign up to set email alerts
|

Current transport efficiency analysis of multijunction solar cells by luminescence imaging

Abstract: Multijunction solar cells are currently leading in efficiency among all types of solar cells. However, the efficiency of those cells under concentrated illumination is limited by the trade‐off between shadowing by the contact grid and series resistances. In this paper, we provide a method using luminescence to image the current transport efficiency for a precise and rapid measurement of the resistance effect. Light beam induced current (LBIC) measurement is used for the first time to calculate current transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As such, they have not previously been reported due to the difficulty to simultaneously account for all underlying physical processes. We expect such spectrally and directionally resolved understanding of photon-recycling processes to be especially beneficial for understanding the internal electrical and optical properties of various thin-film devices, such as the emerging ultrathin GaAs photovoltaic devices [21][22][23][24], and to complement existing advanced modeling and characterization frameworks of multijunction solar cells [25,26].…”
Section: B Characteristics Under Illuminationmentioning
confidence: 99%
“…As such, they have not previously been reported due to the difficulty to simultaneously account for all underlying physical processes. We expect such spectrally and directionally resolved understanding of photon-recycling processes to be especially beneficial for understanding the internal electrical and optical properties of various thin-film devices, such as the emerging ultrathin GaAs photovoltaic devices [21][22][23][24], and to complement existing advanced modeling and characterization frameworks of multijunction solar cells [25,26].…”
Section: B Characteristics Under Illuminationmentioning
confidence: 99%
“…We expect this to be beneficial for understanding and optimizing the internal electrical and optical properties of various thin-film devices, such as the emerging ultra-thin GaAs photovoltaic devices, [21][22][23] and to complement existing advanced modeling and characterization frameworks of multi-junction solar cells. 10,24 To study how the optical power propagates within the solar cell structure studied here, Fig. 7 shows the the Kresolved spectral radiance of internally emitted photons as a function of position and K at the same photon energy 1.43 eV for (a) TE and (b) TM polarization, again for 0.9 V. It can be seen that in the escape cone determined by K/k 0 ≤ 1, there is a clear positive optical power flow out of the device in the bottom right corner of the figures.…”
Section: B Characteristics Under Illuminationmentioning
confidence: 99%
“…10 The current mismatch among subcells can be mitigated by the LC effect, which results in excess photocurrent generation in a current-limiting subcell. 11 Thus, upon fabrication, it can be used to our advantage by relaxing the requirement for current-matched subcells in MJSCs. 12 Previous studies demonstrated varying LC effect efficiencies in Si-based 13 and Ge-based 14 lattice-matched MJSCs.…”
Section: Introductionmentioning
confidence: 99%